Our Rights and Duties in Water resources, Question on Water and Compendium of law related to Conservation and utilization of water resources in Nepal - Thanju, Jeewan Parsad (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not avaiable DOI: http://dx.doi.org/10.3126/hn.v13i0.10063 HYDRO NEPAL Journal of Water, Energy and Environment Issue No.13, July 2013 Page: 88 Uploaded Date: 2014-03-14